Multidimensional roles of cfDNA fragmentomics in preeclampsia: from placental hypoxia and TLR9 inflammation to clinical risk stratification - Guo, Ziyi; Zhang, Bin; Yang, Di; Wang, Li (Frontiers in Medicine, 2025)
Cell-free DNA (cfDNA) has emerged as a pivotal biomarker for predicting preeclampsia (PE), a multisystem syndrome characterized by placental hypoperfusion and systemic inflammation. This review synthesizes critical advances in the field, highlighting quantitative alterations in cfDNA, fragmentomic profiles, and placenta-specific methylation patterns (e.g., RASSF1A) that demonstrate significant value for early prediction and severity stratification of PE. Mechanistically, placental hypoxia-induced trophoblast apoptosis (releasing cfDNA), epigenetic dysregulation activating TLR9/NF-κB inflammatory pathways, and oxidative stress-mediated mitochondrial cfDNA fragmentation collectively drive disease progression. In clinical translation, integrating cfDNA with complementary biomarkers enhances predictive performance, though limitations persist regarding preanalytical variability and dynamic gestational changes. Future efforts must advance fragmentomics-integrated multi-omics frameworks for precision prediction, where assay standardization constitutes the fundamental translational bottleneck.